2010
DOI: 10.1128/jvi.02050-09
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Classical Swine Fever Virus NS4B Affect Virulence in Swine

Abstract: NS4B is one of the nonstructural proteins of classical swine fever virus (CSFV), the etiological agent of a severe, highly lethal disease of swine. Protein domain analysis of the predicted amino acid sequence of the NS4B protein of highly pathogenic CSFV strain Brescia (BICv) identified a putative Toll/interleukin-1 receptor (TIR)-like domain. This TIR-like motif harbors two conserved domains, box 1 and box 2, also observed in other members of the TIR superfamily, including Toll-like receptors (TLRs). Mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 51 publications
0
21
0
1
Order By: Relevance
“…This is reflected in numerous reports in which mutations of different functional domains in the structural proteins C, E rns , E1, and E2 and in the nonstructural proteins p7 and NS4B were shown to reduce the pathogenicity in pigs, indicating that these genes may be involved in determining CSFV virulence (7,8,9,10,11,12,13,32,36,37,38,39,40,46,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is reflected in numerous reports in which mutations of different functional domains in the structural proteins C, E rns , E1, and E2 and in the nonstructural proteins p7 and NS4B were shown to reduce the pathogenicity in pigs, indicating that these genes may be involved in determining CSFV virulence (7,8,9,10,11,12,13,32,36,37,38,39,40,46,54).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the genomes of the GPE Ϫ vaccine virus and the parent ALD virus revealed 225 nucleotide substitutions and 46 amino acid differences (22), which did not provide any conclusive information on the molecular basis of the attenuation. Numerous reports suggest that the viral proteins N pro , C, E rns , E1, E2, p7, and NS4B may be involved in determining the virulence of CSFV in pigs (7,8,9,10,11,12,13,32,36,37,38,39,40,43,46,54). So far, however, all conclusions on CSFV virulence determinants rely on mutations that result in downregulation of pathogenicity.…”
mentioning
confidence: 99%
“…However, NS4B is a poorly characterized protein and its roles in CSFV replication and pathogenesis are not well understood. A putative Toll/interleukin-1 receptor-like domain was identified in the C-terminal region of NS4B (Fernandez-Sainz et al, 2010). Mutations in this domain of NS4B in the highly virulent Brescia strain resulted in an attenuated phenotype along with enhanced activation of TLR-7-induced genes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on different pestiviruses have revealed that NS4B is an endoplasmic reticulum (ER)-associated integral membrane protein that contains four putative transmembrane domains flanked by cytoplasmic N-and C-terminal regions [119,120,121,122]. Interaction of CSFV NS4B with molecular components of the immune system has also been reported [123].…”
Section: A Few Salient Features Of the Structure Composition And Funmentioning
confidence: 99%
“…The synthesis of NS4B protein during viral replication in the tonsil down regulates the expression of IL-6 and this is especially true with CSFV strain Brescia [123]. Swine Leukocyte Antigen I (SLA I) molecules present the endogenous peptides to activate the CD8 + T cells that control viral replication within cells.…”
Section: Immune Evasion and Immunopathogenesis Of Csfmentioning
confidence: 99%